2012
DOI: 10.1097/mnm.0b013e32834ec5d6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 800 and 3700 MBq iodine-131 for the postoperative ablation of thyroid remnant in patients with low-risk differentiated thyroid cancer

Abstract: Our findings suggest that remnant thyroid tissue in patients with low-risk, well-differentiated thyroid cancer after total thyroidectomy can be ablated with 800 MBq of I-131. The success rate is not different from that obtained with 3700 MBq I-131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 21 publications
0
20
0
3
Order By: Relevance
“…Therefore, many experts advocate the utilization of low-dose RAI in low-risk DTC patients because survival benefits of adjuvant RAI therapy is uncertain in this group. Recent studies demonstrated that low-dose RAI is sufficient for remnant ablation therapy for low-risk DTC patients (10,11). Schlumberger et al compared the success rate of 1.1 GBq and 3.7 GBq in DTC patients with pT1 anyN M0 and T2 N0 M0 disease (10).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, many experts advocate the utilization of low-dose RAI in low-risk DTC patients because survival benefits of adjuvant RAI therapy is uncertain in this group. Recent studies demonstrated that low-dose RAI is sufficient for remnant ablation therapy for low-risk DTC patients (10,11). Schlumberger et al compared the success rate of 1.1 GBq and 3.7 GBq in DTC patients with pT1 anyN M0 and T2 N0 M0 disease (10).…”
Section: Discussionmentioning
confidence: 98%
“…At least 12 prospective studies have shown that an activity of 1110 MBq/30 mCi met certain arbitrary endpoints roughly as effectively as the historically often-used 3700 MBq/ 100 mCi, provided the size of the post-surgically remaining tissue Bremnant^is not too large [49]. A few papers have even reported similar ablation rates using ∼20 mCi [34,50], while in contrast, some report a significantly lower ablation rate at 30 mCi than when using 100 mCi. Most importantly, for patients ≥ 45 years, the rate of disease recurrence and DTCspecific mortality was found in some studies to be significantly higher in patients treated with lower RAI activity (≤2000 MBq or 54 mCi), as compared to higher ablative RAI activities [5].…”
Section: Does Adjuvant or Therapeutic Rai Administration Improve Clinmentioning
confidence: 95%
“…In low-risk patients, several series, including two recent prospective, multicenter studies (3,4,5,6,7,8,9,10,11,12,13,14,15), have compared the effectiveness of RAI ablation when using low RAI activities (1110-1850 MBq) or high RAI activities (R3700 MBq) and, in general, their results indicate that low RAI activities are as effective as high RAI activities. In patients defined as high risk according to ATA and ETA guidelines (1, 2), high RAI activities are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Thyroid Association (ATA) and European Thyroid Association (ETA) guidelines (1, 2), sufficient evidences have been accumulated indicating that in low-risk patients who are candidates for thyroid ablation, low RAI activities between 1100 and 1850 MBq have similar ablative effects (3,4,5,6,7,8,9,10,11) and similar (very low) recurrence rates during follow-up (12,13). Very recently, this concept has been reinforced by two prospective, randomized, multicenter studies (14,15), which compared the effectiveness of RAI ablation using 1110 or 3700 MBq of 131 I.…”
Section: Introductionmentioning
confidence: 99%